NĪTI IN MOTION: FEMINIST ETHICS AND MORAL DIPLOMACY IN THE RAMCHARIT MANAS - Dr. Vatsala Shoukla (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
This paper explores nīti in motion—a feminist and decolonial reading of nīti as a dynamic ethic of moral diplomacy, as portrayed in the Sundarkāṇḍ of the Rāmcharitmanas. Rather than viewing nīti as a static code, the study foregrounds its context-sensitive application in moments of ethical tension, embodied by figures like Hanumān, Mandodarī, and Vibhīṣaṇa. Through close readings of key episodes—the encounter with Maināk Parvat, Mandodarī’s counsel to Rāvaṇa, Vibhīṣaṇa’s moral dissent, the prayerful sea crossing, and humane treatment of envoys—the paper uncovers an Indic framework of ethical statecraft. Juxtaposing these narratives with feminist international relations and contemporary diplomacy, the paper demonstrates how the Rāmcharitmanas articulates a model rooted in care, restraint, and accountability. The Sundarkāṇḍ challenges masculinist notions of sovereignty by elevating emotional intelligence, truthfulness, and moral courage as political virtues. Combining textual analysis with ethical reflection, the study asks: How do these characters model relational diplomacy? What insights do they offer for feminist international thought? Ultimately, nīti in motion emerges as a transformative praxis that reimagines diplomacy through indigenous ethics, feminist care, and dialogical engagement—offering timely lessons for global politics today.